Polytrauma during pregnancy - Sarita Agrawal; Vinita Singh; Prashant Kumar Nayak; Pushpawati Thakur; Manju Agrawal; Asha Jain (Journal of Orthopedics, Traumatology and Rehabilitation, 2013)
Trauma during pregnancy is an important cause of nonobstetrical cause of maternal mortality & morbidity. Apart from type of injury affecting the maternal & fetal outcome there are several life threatening complications unique to pregnancy like abruption placentae, uterine rupture, amniotic fluid embolism, & direct fetal trauma which needs immediate interventions. Maternal assessment & management during pregnancy needs special consideration to physiological changes during pregnancy as well as fetal surveillance to improve the maternal & fetal outcome. All pregnant trauma patient needs multi disciplinary approach involving obstetrician, neonatologist, obstetric anaesthetist & trauma surgeons.